Anti-Semitism in Contemporary Malaysia Malay Nationalism, Philosemitism and Pro-Israel Expressions - Ainslie, Mary J.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
Offering an empirical study into anti-Semitism and anti-Israel attitudes in Malaysia, this book examines the complicated nature and function of such beliefs within the contemporary context, mapping these discourses onto different ethnic and economic divisions. Based largely upon qualitative interviews with thirty Malaysian participants who detail their own experiences with and perceptions of this phenomenon, the project reveals how political actors and organizations in Malaysia achieve political success and maintain political power through investing in the Palestinian cause, simultaneously demonizing Israel and Jews to an astounding degree. However, the book also reveals how, in contrast to this state-led agenda, challenging anti-Semitism and pushing for dialogue with Israel has become a means by which progressive citizens can critique authorities and reassert their desire for a liberal and heterogenic Malaysia. The book therefore argues that both interest in and even support for Judaism and Israel may be more prominent than the official Malaysian position may suggest, with citizens holding far more complex opinions and views upon this subject matter.
Introduction - Judaism and anti-Semitism in Southeast Asia and Malaysia -- Anti-Semitism as morally correct - characterizing the dominant construction of Israel, Palestine and Jews in Malaysia -- Understanding the Function of anti-Semitism and the Israel/Palestine situation in Malaysia -- Questioning anti-Semitism in Malaysia -- Curiosity, interest and Philosemitism -- Conclusion.
Keywords: Religion and sociology; Ethnology -- Asia; Culture; Asia -- Politics and government; Sociology of Religion; Asian Culture; Asian Politics